Dynamic Lecturer Evaluation from Student Feedback System via Mobile Application for UTP - Kamarulzaman, Nurhani Izzati (IRC, 2019)
This project aims to explore the gap between UTP students and lectures as well introducing a conceptual feedback framework for UTP students and lecturers on a technology-based evaluation system via mobile application. By using dynamic lecturer assessment from student feedback via mobile application platform, this mobile application attempts to build a stronger connection between teaching and learning. The student feedback system aims to develop and strengthen the distance between the relationship between lecturers and students in the case of input from students during classes, as this will create a better and more effective learning outcome. Current lecturer evaluation in UTP is yet to be seen as the source of improvement but rather to be used for lecturer performance for year-end evaluation where the questions asked and the feedback from the students are rarely given to lecturer and the improvement suggested is not received by the lecturer, the ability to receive real time responses just after the class finished is not available as well as the feedback rating is not properly developed, and the cause of the rating is not shown due to a poorly design feedback forms. This student feedback system via mobile app aims to improve the current student feedback system that will enable this interactive assessment for students to voice their comments and questions throughout the semester. As the feedback will be provided in real time, this will help the lecturers deliver better by direct monitoring and evaluation of the feedback and questions. Then the findings of this student feedback system for assessing the lecturer could be used as part of the assessment of the lecturer.